The Status of CIF Contracts between the Sale of Goods and the Sale of Documents - Çelik, Muhammet Emir (Frontiers in Law, 2023)
The intricate nature of international trade is encapsulated in the complexities of CIF (Cost, Insurance, and Freight) contracts, which stand at the intersection of the sale of goods and the sale of documents. This paper seeks to dissect the pivotal roles played by documents and goods within CIF contracts and to ascertain whether these contracts are more accurately defined as sales of documents rather than sales of goods. By examining legal cases and dissecting the contractual obligations of parties involved in CIF contracts, this study aims to shed light on the essence of these contracts in the context of international law and trade practices. The research is divided into four main parts. Initially, it analyzes the duties of parties and the role of CIF documents in the sale of goods. The second part delves into the implications of documents and goods concerning the transfer of risk and property, probing into the critical claim of documents. The third part scrutinizes the buyer’s right to refuse the documents or the goods, and which aspect takes precedence. The fourth part evaluates the claim that CIF contracts made en route are essentially ’sales of documents’. This study culminates by presenting arguments on the nature of CIF contracts, weighing the significance of documents against the goods themselves. Despite the increasing tendency to use documents to represent physical goods in trade, this paper concludes that CIF contracts inherently constitute contracts for the sale of goods. It highlights the distinctive rights related to the rejection of either documents or goods, thereby reinforcing the primacy of the actual goods over their documentary representations in CIF contracts.